Studies on post harvest management of oyster mushroom (Pleurotus florida) - Sharma, R L; Thakur, M P (Mushroom Research, 2012)
The effect of chemical preservatives, freezing/ deep-freezing and thickness of packaging materials on storage and shelf life of Pleurotus florida has been studied. The chemical preservatives used for enhancing the shelf life of sporophores of P. florida worked better under blanched conditions than unblanched one. Amongst the combination of different chemical preservatives, T-11 (5 % salt, 0.2 % citric acid (CA) and 0.1 % potassium metabisulphite (KMS) and T-13 (1 % salt, 0.1 % Acetic acid (AA), 0.1 % CA, 0.05 % sodium benzoate (SB) and 0.05 % KMS (with blanching) were highly effective in preserving the sporophores of P. florida   till 125-150 days. Freezing (10°C) and deep freezing (-15 °C) conditions highly favoured the storage of the sporophores for a period of 7 and 11 days, respectively, without much influence on the colour, texture, appearance and overall acceptability. Packaging materials of higher density (250 µm) with no perforation had better shelf life of sporphores of P. florida (4 days) as compared to only 2 days in low density (80 µm) perforated bags at ambient temperature.